INTENSITAS SERANGAN HAMA PADA AGROFORESTRI TEGAKAN JATI (Tectona grandis) DI JALAN RAJAWALI SAKTI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU PROVINSI RIAU - Sasmita, Fani; M. Mardhiansyah, M. Mardhiansyah; Darlis, Viny Volcherina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Agroforestry is one of the land management systems that can be offered to overcome the problem of forest land convertion. The success of agroforestry plant growth is influenced by aspects of which are protection from pests. Pest attacks can decrease the potential of standing, both quality and quantity. This study aims to determine the intensity of pest attacks on agroforestry of teak stand (Tectona grandis). Research activities carried out on the Rajawali Sakti street Simpang Baru village Tampan districts. The method used in this research is random sampling. The area covered is 3 Ha with sample intensity of 10% that is 0,3 Ha. An observation plot was made of 10 m x 10 m of 30 plots. The research indicate that the intensity of pest attack on stand of teak is amount to 22,13% which is included in the category of minor damage. Pests that attack teak plants such as caterpillar teak (Hibea puera), white lice (Paracoccus marginatus), white butterfly (Bemisia tabaci), termites (Neotermes tectonae) dan black ants (Polyrhachis Spp). Keywords : Agroforestry, Teak stands (Tectona grandis), Pest, Intensity of attack (IS).